Optical Microlithography XVIII 2005
DOI: 10.1117/12.601175
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mask topography on CD control

Abstract: Past work on mask topography has documented the effects of the topography on the aerial image intensity and on the responses of CD through defocus and image placement. Device performance, however, is limited by the statistical CD variation in the poly lines that form the logic and memory gates. We have developed a tool that combines fast, rigorous EMF calculations with Monte Carlo simulation to investigate the impact of mask topography on CD control. We have applied it to study the effects of mask topography o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In what follows we will derive the essential effects of phase errors on image contrast by means of a simple model based on two beam interference assuming an ideal lens. Similar discussions can be found in, for example, [2,9,10]. Polarization dependent reflection at the resist surface as well as vector effects are neglected.…”
Section: Theorymentioning
confidence: 80%
“…In what follows we will derive the essential effects of phase errors on image contrast by means of a simple model based on two beam interference assuming an ideal lens. Similar discussions can be found in, for example, [2,9,10]. Polarization dependent reflection at the resist surface as well as vector effects are neglected.…”
Section: Theorymentioning
confidence: 80%
“…8 (b). It is reported that phase change caused by 3D mask effect can be interpreted as sort of aberration and also coupled with defocus [3]. This implies that the phase of BLM might not be determined correctly.…”
Section: Defocus Behaviormentioning
confidence: 93%
“…1. It has been reported in numerous publications that this so-called 3D mask effect has non-negligible impact on lithographic performances [1][2][3][4]. This 3D mask effect can be simulated if the near-field image of mask is obtained.…”
Section: Introductionmentioning
confidence: 96%